Effects of Wuwei Dilong Decoction on Inflammatory Cells and Cytokines in Asthma Model Guinea Pigs - 李祥华 涂献玉 张德新 许甲风 王文英 张渊 杜亚明 (Journal of traditional Chinese medicine, 2009)
Objective： To explore the effects and the mechanism of Wuwei Dilong Decoction （五味地龙汤 Schisandra Fruit and Earthworm Decoction） for treatment of asthma. Methods： The asthma guinea pig model was established with spray of ovalbumin （OVA）. Fifteen days later, the guinea pigs were administered by intra-gastric perfusion of Wuwei Dilong Decoction once a day for 8 consecutive days. Blood samples were taken for testing the total leucocytes, eosinophil （EOS）, lymphocytes, interferon-γ （IFN-γ） and leukotriene B4 （LTB4）. Results： In the asthma model group, the total leucocytes, EOS and lymphocytes were all increased, with significant differences as compared with the different dosage Wuwei Dilong Decoction groups （P〈0.01 or P〈0.05）. The serum LTB4 in the asthma model group was significantly increased and IFN-γ decreased. After administration of Wuwei Dilong Decoction of the large, medium and small dosages, LTB4 decreased, while IFN-7 increased （P〈0.05 or P〈0.01）. Conclusion： Wuwei Dilong Decoction can inhibit infiltration and diffusion of the inflammatory cells in the asthma model guinea pigs, and regulate LTB4 and IFN-γ, which is probably one of the important mechanisms of Wuwei Dilong Decoction for relieving asthma.